Ammonium-based aeration control improves nitrogen removal efficiency and reduces N2O emissions for partial nitritation-anammox reactors. (July 2021) - Wan, Xinyu; Baeten, Janis E.; Laureni, Michele; Volcke, Eveline I.P.
Abstract: This study deals with the effect of aeration control strategies on the nitrogen removal efficiency and nitrous oxide (N2 O) emissions in a partial nitritation–anammox reactor with granular sludge. More specifically, dissolved oxygen (DO) control, constant airflow and effluent ammonium (NH4 + ) control strategies were compared through a simulation study. Particular attention was paid to the effect of flocs, which are deliberately or unavoidable present besides granules in this type of reactor. When applying DO control, DO setpoints had to be adjusted to the amount of flocs present in the reactor to maintain high nitrogen removal and reduce N2 O emissions, which is difficult to realize in practice because of variable floc fractions. Constant airflow rate control could maintain a good nitrogen removal efficiency independent of the floc fraction in the reactor, but failed in N2 O mitigation. Controlling aeration based on the effluent ammonium concentration results in both high nitrogen removal and relatively low N2 O emissions, also in the presence of flocs. Fluctuations in floc fractions caused significant upsets in nitrogen removal and N2 O emissions under DO control but had less effect at constant airflow and effluent ammonium control. Still, rapid and sharp drops in flocs led to a peak in N2 O emissions at constant airflow and effluent ammonium control. Overall, effluent ammonium control reached the highest average nitrogen removal and lowest N2 O emissions and consumed the lowest aeration energy under fluctuating floc concentrations. Highlights: Aeration control and floc abundance impact N removal and N2 O emissions. Constant Qair or effluent NH4 + control suppresses NOB at varying floc content, constant DO do not. Sharp drops in floc fractions cause N2 O peaks at constant Qair and NH4 + control. Effluent NH4 + control led to the highest N removal and the lowest N2 O emissions.